Prevalence of antibodies to poliovirus in 1978 among subjects aged 0-88 years. Issue 6317 (6th March 1982) - Roebuck, M; Chamberlain, R
Abstract : The antibody state of a population aged 6 months to 88 years to poliovirus types 1, 2, and 3 was determined by examining 919 sera collected in Lancashire, London, and southern and south-east England. In subjects aged over 2 years the immune state was surprisingly uniform, although the older patients had probably acquired practically all their antibodies as a result of natural infection and those under 16 through vaccination. at least 95% had detectable antibodies to at least one poliovirus type and about 60% to all three types, with the exception of a cohort of children born between 1963 and 1968, in whom the proportions were about 80% and 40% respectively. These children were born around the time of the changeover from inactivated to oral vaccine, when immunisation rates were low and there was confusion over the number of doses required. These results indicate that a complete course of vaccine or a booster dose at or around school-leaving age is necessary.